Ethics of Artificial Intelligence: Dialectics of Artificial Intelligence Policy for Humanity - Syafuddin, Khairul (The Eastasouth Journal of Information System and Computer Science, 2024)
Artificial Intelligence is now widely used by humans. The use of this technology is based on the view that Artificial Intelligence can make their lives easier. Many sectors have utilized this technology, including government, private, social, health, to education. Even though Artificial Intelligence is felt to have many benefits, there are perceived threats so that appropriate policies are needed. Thus, the aim of this research is to find out policies that can be recommended for the use of Artificial Intelligence that focus on humanitarian aspects. This research uses a qualitative approach to deepen the literature review that has been carried out. The results of this research show that the presence of Artificial Intelligence provides quite large benefits, especially as a technology for predicting the future. However, to regulate the use of this technology, appropriate policies are needed to avoid increasingly widespread digital crimes. In formulating Artificial Intelligence policies, humanitarian aspects need to be considered to provide appropriate protection. Especially for vulnerable groups who have low access to the use of Artificial Intelligence.